THE EFFECT OF INTRAMOLECULAR H-BOND INTERACTIONS IN THE ISOMERIZATION PROCESS IN AMINO ACIDS - Paranthaman, Selvarengan (Journal of the Chilean Chemical Society, 2018)
The effect of intramolecular hydrogen bond (H-bond) interactions in the cis - trans isomerization of the amino acids such as, cysteine, serine, threonine and valine have been studied using density functional theory method. Our calculations have shown that the geometrical parameters are significantly changed during the isomerization process. This is due to the presence of intramolecular H-bonds within main chain or in between side chain and main chain. The barrier energies have been calculated for isomerization process in all the amino acids, which is more for cysteine and less for valine. The Fourier decomposition potential has been obtained for the above named amino acids which show that V2 potential has higher value. The vibrational frequency analysis has been carried out for the cis and trans forms of cysteine, serine, threonine and valine amino acids and the results are discussed.